Determinants of doctorate holders’ job satisfaction. An analysis by employment sector and type of satisfaction in Spain - Escardíbul, Josep-Oriol (2015)
In this study we analyze the determinants of job satisfaction of doctorate holders in Spain. Specifically, we consider overall job satisfaction as well as basic and motivational satisfaction following Herzberg’s typology (based on Maslow’s hierarchy of needs). Using data from the Spanish Survey on Human Resources in Science and Technology of 2009, representative of the Spanish doctoral graduate population, we develop an analysis by gender and institutional sector (university and non-university) where employees are employed. We propose OLS regression to identify the determinants of basic and motivational satisfaction at job as well as an ordered logit model for overall job satisfaction. Results do not allow us to confirm Herzberg’s differentiation for the Spanish PhD holders, since factors related with basic motivation (such as salary or working conditions referred to ‘safety’) have a bearing on all types of job satisfaction (not only the basic one as expected). Likewise, results do not show significant differences by gender. However, it seems that these ‘basic’ needs are less important for the job satisfaction those PhD holders working at the University. Our results seem reasonable for a Southern European country where monetary conditions in labor relations are worse than in other developed countries.